Induction and carbon catabolite repression of phenol degradation genes in Rhodococcus erythropolis and Rhodococcus jostii - Szőköl, Juraj; Rucká, Lenka; Šimčíková, Michaela; Halada, Petr; Nešvera, Jan; Pátek, Miroslav (Applied microbiology and biotechnology, 2014)
Rhodococcus erythropolis CCM2595 is able to efficiently utilize phenol and other aromatic compounds. We cloned and sequenced its complete gene cluster - catA, catB, catC, catR, pheR, pheA2, pheA1 - involved in the ortho-cleavage pathway of phenol. The activity of the key enzyme of the phenol degradation pathway, two-component phenol hydroxylase, was found to be induced by phenol. When both phenol and succinate were present in the medium, phenol hydroxylase activity decreased substantially. To analyze the regulation of phenol degradation at the transcriptional level, the transcriptional fusions of the divergently oriented promoters PpheA2 and PpheR with the gfpuv reporter gene were constructed. The promoters driving expression of the genes of the pheR-pheA2pheA1 cluster were localized by determining the respective transcriptional start points. Measurements of GFP fluorescence as well as quantitative RT-PCR revealed that expression of the phe genes is induced by phenol at the transcriptional level. The transcription of pheA2A1 and pheR was repressed by succinate, whereas no repression by glucose or glycerol was observed. Activation of the R. erythropolis CCM2595 pheA2 promoter by PheR, an AraC-type transcriptional regulator, was demonstrated by overexpression of the pheR gene. Analysis of the transcriptional regulation of two similar phe clusters from R. jostii RHA1 by various substrates showed that the type of carbon catabolite repression and the temporal transcriptional pattern during cultivation are different in each of the three phe clusters analyzed.
Keywords: multigenová rodina; regulace genové exprese u bakterií; bakteriální proteiny; fenol; Mixed Function Oxygenases; Bacterial Proteins; Biodegradation, Environmental; Catabolite Repression; Rhodococcus; Gene Expression Regulation, Bacterial; Phenol; promotorové oblasti (genetika); Promoter Regions, Genetic; biodegradace; oxygenasy se smíšenou funkcí; katabolická represe; Multigene Family